Photo- and triboluminescent robust 1D polymers made of Mn(ii) halides and meta-carborane based bis(phosphine oxide). Issue 9 (12th March 2021) - Artem'ev, Alexander V.; Davydova, Maria P.; Berezin, Alexey S.; Sukhikh, Taisiya S.; Samsonenko, Denis G.
Abstract : The 1D CPs of [Mn(L)X2 ] n type (X = Cl, Br, I), designed on 1, 7-bis(diphenylphosphinyl)- m -carborane (L), show bright phosphorescence and triboluminescence, as well as exhibit thermo- and solvatochromic luminescence. Abstract : A series of 1D coordination polymers (CPs), [MnX2 (L)] n (X = Cl, Br, I), made of MnX2 units bridged by 1, 7-[Ph2 P(O)]2 - meta -carborane ligands (L) through the O–Mn–O linkages, have been designed. At ambient temperature, these CPs manifest green phosphorescence with quantum yields of up to 60%, which is the highest value for Mn(ii ) CPs. CP [MnI2 (L)] n and its structurally different solvate [MnI2 (L)·CH2 Cl2 ] n also exhibit bright triboluminescence. Thermochromic luminescence of the designed CPs appears as reversible shifting of their emission color, when the temperature varies from 350 to 77 K and back. Moreover, [MnI2 (L)·CH2 Cl2 ] n reversibly changes its emission properties during desolvation-solvation processes thus featuring solvatochromic luminescence. According to photophysical and EPR data, the observed phosphorescence originates from the ligand-sensitized 4 T1 → 6 A1 transition in Mn 2+ ions. Enhanced robustness of the title CPs is demonstrated by retaining their emission properties after prolonged heating at 210 °C.